Transforming Growth Factor-Beta-Regulated LncRNA-MUF Promotes Invasion by Modulating the miR-34a Snail1 Axis in Glioblastoma Multiforme - Shree, Bakhya; Tripathi, Shraddha; Sharma, Vivek (Frontiers in Oncology, 2022)
TGF-β regulated long-non-coding RNAs (lncRNAs) modulate several aspects of tumor development such as proliferation, invasion, metastasis, epithelial to mesenchyme transition (EMT), and drug resistance in various cancers, including GBM. We identified several novel differentially expressed lncRNAs upon TGF-β treatment in glioma cells using a genome-wide microarray screen. We show that TGF-β1 induces lncRNA-MUF in glioma cells, and its expression is significantly up-regulated in glioma tissues and is associated with poor overall survival of GBM patients. Knock-down of lncRNA-MUF reduces proliferation, migration, invasion in glioma cells and sensitizes them to Temozolomide (TMZ) induced apoptosis. In addition, lncRNA-MUF downregulation impairs TGF-β induced smad2/3 phosphorylation. In line with its role in regulating invasion, lncRNA-MUF functions as a competing endogenous RNA for miR-34a and promotes Snail1 expression. Collectively, our findings suggest lncRNA-MUF as an attractive therapeutic target for GBM.